Nature And Personification Aesthetics in Niyi Osundare’s Green: Sighs of our Ailing Planet - Favour Adaramola; Olanike Olaleru (University of Chitral Journal of Linguistics and Literature, 2025)
This study examines Niyi Osundare’s deployment of personification as a poetic symbol to examine Nature in different ramifications as seen in his Green: Sighs of Our Ailing Planet. The poetry volume explores the poet’s concerns about humankind’s objectionable dealings with the environment, not only in Africa but also across the earth. He particularly focuses on prevalent environmental concerns underscored by recent crises and disasters befalling communities in different parts of the world. The poetry volume, through different poems, emphasizes humankind’s complicit role in the devastating consequences of environmental abuse. Employing an Ecocritical approach, the paper investigated dominant themes such as neglect, insensitivity, misappropriation, exploitation among others, as well as the use of the poetic element of personification as a literary style to expose and criticize nature’s present precarious state. The research results reveal that human activities such as environmental abuse, tree felling, and anthropocentrism, among others, are constituting a danger and subsequent destruction to nature, which also negatively affects human life on earth. Through the deployment of personification, in which the poet presents nature as having human characteristics and emotions, the poet advocated that responsible consideration and care should be bestowed upon nature rather than engaging in activities that harm it. The analysis lays bare the poetry volume’s explicit stand against the popular belief of humankind exclusively owning the universe without necessarily being its being its guardians and protectors. The research findings show that Green: Sighs of Our Ailing Planet presents a clear insight into the realities of the symbiotic relationship existing between humankind and the environment. The study contributes significant knowledge to an understanding of the existential co-dependence between nature and humankind.